Compensatory growth and production of white shrimp, Litopenaeus vannamei, in Costa Rica, during the maternity, development and grow-out commercial phases - Valverde-Moya, José A. (2015)
Compensatory growth and production of Litopenaeus vannamei in commercial cultures in farms in the Gulf of Nicoya, Costa Rica, during 2014 were evaluated in this study. Growth and production were compared between three culture systems starting from an initial maternity (MA) phase with high stocking density (85/m2) of post larvae: a) maternity-development (MA-DE) with a medium stocking density (23.3/m2) and an initial weight of 1.4 g, b) maternity-development-grow-out (MA-DE-G) with a low density (8.6/m2) and an initial weight of 6.0 g and c) maternity-grow-out (MA-G) (9.4/m2 and 1.4 g). An increase in growth was recorded in MA-DE (0.85 g/week) as compared to MA (0.26 g/week), and the specific growth rate (SGR) was 3.73 %g/day for MA-DE. Survival (81.0%) and production (1 029 kg/ha) in MA-DE were higher than in MA (75.3% and 842 kg/ha, respectively). Weekly growth showed no differences between both grow-out systems: MA-G = 1.07 and MA-DE-G = 1.02 g/week; however, SGR was lower in MA-DE-G (1.51 %g/day) than in MA-G (3.19 %g/day). Results indicate the lack of compensatory growth from MA to MA-DE, and from MA-DE to MA-DE-G, while partial compensatory growth was recorded from MA to MA-G. Taken into account this compensatory growth gain in juveniles, the culture of L. vannamei in MA at high density seems to be a good production strategy.